L’européanisation de l’action publique en Grèce (1980‑2010) : l’impact sur les politiques culturelles territoriales - Dionysia Tzemopoulou (Cahiers Balkaniques)
The accession of Greece to the EEC/EU (1981) resulted in the application of European directives in all areas of public action. By 1989, Greek state-led development initiatives were fully integrated into Community Support Frameworks (CSFs) and sectoral EU funding programs. This article proposes an analysis of the Europeanization process and its impact on the evolution of local cultural policies during the period 1980‑2010. In this perspective, we wish to understand the nature of the changes identified in the process of decision-making, since a new component that of Community action, plays a dynamic role in defining the content of public policies.